Enhancing the hydration process of common beans by ultrasound and high temperatures: Impact on cooking and thermodynamic properties - Miano A.C. (2018)
The authors are grateful to the São Paulo Research Foundation for funding the projects n° 2016/18052-5 and 2014/16998-3, as well as the V. Sabadoti B. Sc. Scholarship (2016/23908–6); the National Council for Scientific and Technological Development for funding the project n° 401004/2014-7; and Cienciactiva for the A.C. Miano Ph.D. scholarship, from the ‘‘Consejo Nacional de Ciencia, Tecnología e Inovación Tecnológica" (CONCYTEC, Peru; Contract 272-2015-FONDECYT).